Cashback and Discounts in Promoting Sustainable Digital Transactions Among Students: A QRIS Case Study - Amalia, Via; Suratno; Eriyani (Journal of Economic Education, 2025)
Developing a digital payment system through QRIS (Quick Response Code Indonesian Standard) is a strategic initiative to encourage financial inclusion and transaction efficiency, especially among the younger generation. However, the sustainable adoption of QRIS still faces challenges, especially related to the effectiveness of economic incentives in influencing user behavior. This study aims to analyze the influence of cashback and discounts on the sustainable use of QRIS among Semarang State University (UNNES) students and examine the role of digital financial literacy as a moderation variable. This research employed a quantitative method using a survey approach involving 92 respondents who were active users of QRIS. Data were analyzed using linear regression and moderation interaction tests. The results showed that cashback had a positive and significant effect on the use of QRIS, while discounts did not show a significant impact. Digital financial literacy has a substantial direct effect on the use of QRIS, but it does not moderate the relationship between incentives (cashback and discounts) and the use of QRIS. These findings emphasize the importance of direct financial incentives such as cashback and digital financial literacy as independent factors in encouraging sustainable digital transaction habits. This research makes an empirical contribution to supporting the achievement of the Sustainable Development Goals (SDGs), especially in terms of financial inclusion and responsible consumption